2013
DOI: 10.1245/s10434-013-3064-9
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Pain Medication Requirements in Patients Undergoing Computer-Assisted (“Robotic”) and Standard Laparoscopic Procedures for Newly Diagnosed Endometrial Cancer

Abstract: RBT is independently associated with significantly lower postoperative pain and pain medication requirements compared to LSC. The amount of intraoperative fentanyl analgesia does not appear to correlate with postoperative pain.Endometrial cancer is the most common gynecologic malignancy in the United States, with an estimated 47,130 new cases in 2012.1 An estimated 287,100 women were diagnosed with endometrial cancer worldwide in 2008.2 Surgery is the primary treatment of choice for the majority of these women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…Single arm cohort studies examining QOL in patients undergoing robotic surgery have shown that there is a return to baseline scores by three to five weeks, suggesting an advantage to this modality over laparoscopy [27,28]. One retrospective study reported reduced pain medication requirements in women treated with a robotic versus laparoscopic approach [29]. However, there have been no prospective studies directly comparing laparoscopic and robotic surgical patients for overall QOL.…”
Section: Discussionmentioning
confidence: 99%
“…Single arm cohort studies examining QOL in patients undergoing robotic surgery have shown that there is a return to baseline scores by three to five weeks, suggesting an advantage to this modality over laparoscopy [27,28]. One retrospective study reported reduced pain medication requirements in women treated with a robotic versus laparoscopic approach [29]. However, there have been no prospective studies directly comparing laparoscopic and robotic surgical patients for overall QOL.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the postoperative outcomes, the robotic group demonstrated significantly lower postoperative and 24 h pain scores. Previous reports had demonstrated that anaesthetic requirements were lower during robotic surgery for cervical and endometrial cancer management, which corresponded to our results . A possible explanation is that robotic surgery provided precise dissection within a limited space and reduced the need for local electro‐coagulation during surgery; as a result, tissue damage was reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Leitao and colleagues (2013) showed that patients undergoing robotic surgery for endometrial cancer had a median maximal pain score of 4 and median total post-operative fentanyl use of 242.5 micrograms. (12) Hachem et al (2013) showed that patients who underwent robotic hysterectomy had a mean pain score of 6.62 on post-operative day (POD) 0 and 5.59 on POD 1. (13) While no studies have evaluated a TAP block's effectiveness in robotic assisted hysterectomy, there have been studies evaluating its use in laparoscopic assisted total hysterectomy with conflicting reported benefits.…”
Section: Discussionmentioning
confidence: 99%